Anti-Soiling Coatings for Enhancement of PV Panel Performance in Desert Environment: A Critical Review and Market Overview - Mohammad Istiaque Hossain (17944964) (2022)
Areas with abundant sunlight, such as the Middle East and North Africa (MENA), are optimal for photovoltaic (PV) power generation. However, the average power loss of photovoltaic modules caused by dust accumulation is extreme and may reach 1%/day, necessitating frequent cleaning which adds to the cost of operations and maintenance. One of the solutions to the problem of PV soiling is to develop anti-soil coatings, where hydrophilic or hydrophobic coatings with spectral characteristics suitable for PV applications are added to the outer layer of PV glass. However, the effectiveness of such coatings depends extensively on climatic conditions and geographical locations. Since coatings add to the cost of solar panels, it is imperative that they are first tested for suitability at the intended location and/or in similar weather conditions prior to their large-scale deployment. This critical review focuses on various anti-dust technologies employed to mitigate the PV soiling issue. The in-depth comparison of the various developed techniques and materials aims at providing a relevant input in adapting the right technology based on particles’ accumulation mechanism, weather conditions, and geographical location. Though the mechanical cleaning process is the most used solution to date, development of thin film anti-dust coating could be a better alternative—when it is relevant—due to its abrasion-free capability, large deployment, economic viability, and durability. This review aims at serving as a reference in this topic, thereby paving the way to adapting efficient anti-dust coatings, especially in the MENA region and/or desert environment at large, where it is the most relevant. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma15207139